Gecekondu Çalışmalarında ’Öteki’ Olarak Gecekondulu Kurguları - Tahire Erman (European Journal of Turkish Studies)
This article reviews gecekondu studies ranging from earlier to recent ones to reveal the various representations of the gecekondu people in these studies. The representation of the gecekondu people varies in different time periods, namely, the ‘rural Otherʼ in the 1950s and 1960s; the ‘exploited/disadvantaged Otherʼ in the 1970s; the ‘diversified Others in terms of ethnicity, religious sect and genderʼ, and the ‘undeserving rich Otherʼ versus the ‘urban poor Otherʼ in the 1980s and 1990s; and finally the ‘threatening Other/varoşluʼ vs. the ‘gecekondu people as agentsʼ in the late 1990s and 2000s. The article presents these representations/constructions by contextualizing them in the specific social, political and economic conditions, as well as academic paradigms of these periods. It concludes by drawing attention to the need to find new a terminology and new perspectives while studying gecekondu people that would not imply inferiority, that would not lead to defining them as the Other(s).